A new species of Eugenia sect. Eugenia (Myrtaceae) from Atlantic Forest in São Paulo, Brazil - Mazine, Fiorella F.; Valdemarin, Karinne Sampaio; Giaretta, Augusto; Sobral, Marcos (Phytotaxa, 2023)
Eugenia aeterna, a new species of Eugenia sect. Eugenia is described and illustrated. It has been recorded in the Ombrophilous Forest of the Atlantic Forest Domain in the municipalities of Caraguatatuba and Ubatuba, São Paulo state, Brazil. The new species is apparently related to Eugenia ligustrina and E. longipedunculata being distinct from both by: cataphylls persistent until mature twigs, even in the vegetative phase of the plant (versus cataphylls deciduous); puberulent or pilose hypanthium (vs. glabrous hypanthium) and calyx lobes reflexed and appressed to the fruit (vs. calyx lobes erect in the fruit). Following IUCN red list criteria, Eugenia aeterna is classified Least Concern. Additionally, a distribution map is provided.